PERAN PROFITABILITAS DALAM MEMODERASI PENGARUH KEBIJAKAN DIVIDEN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Arista Pradnyani, I Gusti Agung; Widhiastuti, Ni Luh Putu (MOTIVASI, 2024)
Purpose– The objective of this research is to evaluate how profitability influences financial decision components affecting company value which can be used as reference material for further academics. This research also aims to provide knowledge and insight to food and beverage companies regarding the level of profitability that can strengthen or weaken the relationship between dividend policy and capital structure on company value. Design/methodology– Research was conducted on food and beverage companies on the Indonesia Stock Exchange for the 2020-2022 period. The type of research carried out is associative. The data used in this research is secondary data obtained from the official BEI website (www.Iidx.co.id). The method used is documentation. The sample was obtained using the purposive sampling method so that a sample of 22 companies was obtained so that observations were made at 66 food and beverage companies. The data analysis used is quantitative analysis. The analysis technique uses multiple linear regression analysis with the help of the SPSS version 26 application. Findings - Based on the data processing carried out, it was found that dividend policy had a negative effect on company value, while capital structure had a positive effect on capital structure. Profitability is concluded to be able to act as a moderating variable on the influence of dividend policy and capital structure on dividend policy.